2018
DOI: 10.3390/s18030813
|View full text |Cite
|
Sign up to set email alerts
|

A Reliable Methodology for Determining Seed Viability by Using Hyperspectral Data from Two Sides of Wheat Seeds

Abstract: This study investigated the possibility of using visible and near-infrared (VIS/NIR) hyperspectral imaging techniques to discriminate viable and non-viable wheat seeds. Both sides of individual seeds were subjected to hyperspectral imaging (400–1000 nm) to acquire reflectance spectral data. Four spectral datasets, including the ventral groove side, reverse side, mean (the mean of two sides’ spectra of every seed), and mixture datasets (two sides’ spectra of every seed), were used to construct the models. Class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 50 publications
2
31
0
2
Order By: Relevance
“…The results showed that the AdaBoost algorithm could greatly improve the classification performance of the original model. Compared with the current related study using NIR or HSI technology (Al‐Amery et al, ; Zhang et al, ), FHSI technology combined with the optimization model reduced the data dimension of the model and improved the discrimination accuracy of viable and nonviable seeds. In summary, the developed model CARS‐SVM‐AdaBoost not only had a satisfactory classification effect, but also had good stability of the model.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The results showed that the AdaBoost algorithm could greatly improve the classification performance of the original model. Compared with the current related study using NIR or HSI technology (Al‐Amery et al, ; Zhang et al, ), FHSI technology combined with the optimization model reduced the data dimension of the model and improved the discrimination accuracy of viable and nonviable seeds. In summary, the developed model CARS‐SVM‐AdaBoost not only had a satisfactory classification effect, but also had good stability of the model.…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, FT‐NIR technology combined with PLS‐DA model was applied for the viability detection of crop seeds such as corn (Ambrose, Lohumi, Lee, & Cho, ) and soybean (Kusumaningrum et al, ), and the satisfactory results were achieved. In addition, HSI technology coupled with suitable model was successfully applied in the identification of viable and nonviable muskmelon seeds (Kandpal, Lohumi, Kim, Kang, & Cho, ), wheat (Zhang et al, ), and other seeds.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of kernel functions exist, namely, linear kernel function, radial basis function (RBF), polynomial kernel function, and polynomial function. In the present study, SVM was built using RBF because previous researches confirm that RBF is a more compatible supported kernel function . The penalty coefficient ( c ) of the SVM model and the kernel width ( g ) of the kernel function must be determined.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, SVM was built using RBF because previous researches confirm that RBF is a more compatible supported kernel function. [26][27][28] The penalty coefficient (c) of the SVM model and the kernel width (g) of the kernel function must be determined. The optimal combination of (c, g) was determined by a grid-search procedure and the ranges of c and g were both 2 −10 to 2 10 .…”
Section: Multivariate Data Analysismentioning
confidence: 99%
“…Hyperspectral images (HSIs) have many spectral bands and complex spatial structures that contain abundant information [ 1 , 2 ]. Therefore, HSIs are widely applied in areas such as ocean monitoring [ 3 , 4 ], precision agriculture [ 5 , 6 ], forest degradation statistics [ 7 ] and military reconnaissance [ 8 ]. However, the high-dimensional spectral features of HSIs may cause the Hughes phenomenon [ 9 , 10 ], leading to a decrease in HSI classification accuracy [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%